THE TRANSITION OF MALAY WOMEN’S ROLE AND CONTRIBUTION IN THE EARLY 20TH CENTURY - Mohd Noor, Arbaâ€™iyah (Journal of Al-Tamaddun, 2020)
This article discusses the transition of Malay Women’s role and contribution in the early 20th century. It will unearth the awakening of the 20th century Malay women towards their education. The chronology will start with the introduction of the Malay women before the 20th century and the causes that triggered their consciousness toward the need for education. Between 1900 and 1930s, the Malays were more acceptable towards the education system initiated by the British. After the 1930s, they became more aware of the importance of education for their children, including their daughters. Other issues to be discussed are the changing role or position of women and their contributions to the era in political, economic and social aspects. The methodology of this research is more on qualitative method by using historical approach. The findings show that through education, the society has been able to change women's role compared to the past. The biggest accomplishment was on the status of the Malay women with the highly educated ones being given the trust to play more significant roles in politics, economy and social aspects.